S123 The effects of electronic cigarette flavourings on macrophage cytokine release and phagocytosis. (15th November 2016) - Dacie, RL; Belchamber, KB; Donnelly, LE
Abstract : Background: Electronic cigarettes (e-cigarettes) are marketed as an alternative to tobacco cigarettes, but little is known regarding their biological effects. Studies to date have produced varying results, reflecting varying chemical compositions of different e-liquids. Chronic tobacco smoking is known to alter macrophage function, resulting in impaired bacterial phagocytosis and increased release of cytokines including TNFα, CXCL8 and IL-6. To date, there is little understanding of the effects of e-cigarettes on human macrophages. It was hypothesised that e-cigarettes would produce effects on macrophage function comparable to those of tobacco cigarettes. Methods: Six e-liquids were investigated: tobacco-flavoured e-liquid (± nicotine), banoffee-pie-flavoured e-liquid (± nicotine), e-liquid vehicle (propylene glycol + vegetable glycerine) and nicotine-vehicle solution. Effects of e-cigarette vapour extracts (e-CVEs) were compared with cigarette smoke extract (CSE) from a tobacco cigarette. Monocyte-derived macrophages (MDMs) from healthy subjects (n = 6) were cultured for 24 h with e-CVEs or CSE then incubated for 4h with Streptococcus pneumoniae or Haemophilus influenzae . Cell viability was determined and phagocytosis was quantified using fluorimetry. Release of TNFα, CXCL8 and IL-6 was measured by ELISA. Expression of macrophage receptor with collagenous structure (MARCO) and toll-like receptors (TLRs) 2 and 4 was measured by flow cytometry. Results: Neither CSE nor any of the e-CVEs had any significant effect on cell viability. In addition, none of the exposures produced any significant effect on phagocytosis, though higher concentrations of CSE displayed a trend towards reduced phagocytosis. CSE significantly reduced TNFα release (by approximately 70%; p < 0.05). Tobacco- and banoffee pie-flavoured e-CVEs also caused significant reductions in TNFα release (by 30–50%; p < 0.05), while nicotine and the e-liquid vehicle had no effect. Minimal effects were observed on CXCL8 and IL-6 release (0–30% reduction; p > 0.05) with CSE and e-CVEs. Expression of MARCO and TLR4 were unaffected by all cell treatments. TLR2 expression appeared to be slightly increased by e-CVEs, but was not statistically significant. Conclusion: Effects of e-CVEs on MDMs differed from those of CSE. E-liquid flavourings appeared to be responsible for changes in MDM function, while the e-liquid vehicle and nicotine solution had minimal effects. More research is needed to improve understanding of the biological effects of e-cigarette flavourings.